Consolidated bioprocessing of lignocellulosic biomass to lactic acid by a synthetic fungal‐bacterial consortium. Issue 5 (1st February 2018) - Shahab, Robert L.; Luterbacher, Jeremy S.; Brethauer, Simone; Studer, Michael H.
Abstract: Consolidated bioprocessing (CBP) of lignocellulosic feedstocks to platform chemicals requires complex metabolic processes, which are commonly executed by single genetically engineered microorganisms. Alternatively, synthetic consortia can be employed to compartmentalize the required metabolic functions among different specialized microorganisms as demonstrated in this work for the direct production of lactic acid from lignocellulosic biomass. We composed an artificial cross‐kingdom consortium and co‐cultivated the aerobic fungus Trichoderma reesei for the secretion of cellulolytic enzymes with facultative anaerobic lactic acid bacteria. We engineered ecological niches to enable the formation of a spatially structured biofilm. Up to 34.7 gL −1 lactic acid could be produced from 5% (w/w) microcrystalline cellulose. Challenges in converting pretreated lignocellulosic biomass include the presence of inhibitors, the formation of acetic acid and carbon catabolite repression. In the CBP consortium hexoses and pentoses were simultaneously consumed and metabolic cross‐feeding enabled the in situ degradation of acetic acid. As a result, superior product purities were achieved and 19.8 gL −1 (85.2% of the theoretical maximum) of lactic acid could be produced from non‐detoxified steam‐pretreated beech wood. These results demonstrate the potential of consortium‐based CBP technologies for the production of high value chemicals from pretreated lignocellulosic biomass in a single step. Abstract : In this work, the direct production of lactic acid from pretreated lignocellulosic biomass by a synthetic microbial consortium was demonstrated. The cellulolytic enzymes producing aerobic fungus Trichoderma reesei and facultative anaerobic lactic acid bacteria with the capability to utilize both hexoses and pentoses were co‐cultivated in a membrane‐aerated biofilm reactor. Metabolic compartmentalization and spatial structuring allowed the formation of stable artificial cooperator‐cheater communities thereby showing the potential of engineering microbial consortia for consolidated bioprocessing of lignocellulosic biomass.